MHC-Mismatched Islet Allografts Are Vulnerable to Autoimmune Recognition In Vivo - Kupfer, Tinalyn M; Crawford, Megan L; Pham, Kim; Gill, Ronald G (The Journal of immunology (1950), 2005)
When transplanted into type 1a diabetic recipients, islet allografts are subject both to conventional allograft immunity and, presumably, to recurrent autoimmune (islet-specific) pathogenesis. Importantly, CD4 T cells play a central role both in islet allograft rejection and in autoimmune disease recurrence leading to the destruction of syngeneic islet transplants in diabetic NOD mice. However, it is unclear how NOD host MHC class II (I-Ag7)-restricted, autoreactive CD4 T cells may also contribute to the recognition of allogeneic islet grafts that express disparate MHC class II molecules. We hypothesized that islet-specific CD4 T cells can target MHC-mismatched islet allografts for destruction via the “indirect” (host APC-dependent) pathway of Ag recognition. To test this hypothesis, we determined whether NOD-derived, islet-specific CD4 T cells (BDC-2.5 TCR transgenic cells) could damage MHC-mismatched islets in vivo independent of conventional allograft immunity. Results demonstrate that BDC-2.5 CD4 T cells can vigorously destroy MHC class II-disparate islet allografts established in NOD.scid recipients. Tissue injury is tissue-specific in that BDC-2.5 T cells destroy donor-type islet, but not thyroid allografts established in the same NOD.scid recipient. Furthermore, BDC-2.5 CD4 T cells acutely destroy MHC class II-deficient islet allografts in vivo, indicating that autoimmune pathogenesis can be completely independent of donor MHC class II expression. Taken together, these findings indicate that MHC-mismatched islet allografts can be vulnerable to autoimmune pathogenesis triggered by autoreactive CD4 T cells, presumably through indirect autoantigen recognition in vivo.